Breast Tumor Diagnosis Using Diode Laser in Near Infrared Region - Dawood, Munqith S.; Mohammed, Ahmed Ali (Al-Khwarizmi Engineering Journal, 2009)
In the last years, new non-invasively laser methods were used to detect breast tumors for pre- and postmenopausal females. The methods based on using laser radiation are safer than the other daily used methods for breast tumor detection like X-ray mammography, CT-scanner, and nuclear medicine. One of these new methods is called FDPM (Frequency Domain Photon Migration). It is based on the modulation of laser beam by variable frequency sinusoidal waves. The modulated laser radiations illuminate the breast tissue and received from opposite side. In this paper the amplitude and the phase shift of the received signal were calculated according to the original signal for the sake of diagnosis. These calculations were carried out for different breast thicknesses to find out the best modulation laser beam wavelength and the optimum breast thickness necessary for diagnosis of benign and malignant tumors. According to our work the most suitable laser wave length to detect the breast tumor for pre- and postmenopausal females was 956 nm and 674 nm for both malignant and benign tumors.